Enzymatic amplification of exogenous and endogenous retroviral sequences from DNA of patients with tropical spastic paraparesis. - Bangham, C R (1988)
Using oligonucleotide primers that hybridize to conserved sequences in the reverse transcriptase (RT) gene, we have amplified by the polymerase chain reaction three sequence variants of HTLV-I from the genomic DNA of five patients with tropical spastic paraparesis (TSP), and a fourth sequence variant from a healthy carrier of HTLV-I. These results unequivocally identify the retrovirus associated with TSP as HTLV-I and suggest that no sequence variant is uniquely responsible for the condition. The same primers served to amplify two novel single-copy endogenous retroviral RT sequences related to the exogenous mammalian leukaemia viruses: and three KpnI (LINE1) family DNA repeats. This strategy, combining the sensitivity of PCR with cross-reactive primers, may be useful in the search for known or novel retroviruses in other diseases of possible retroviral aetiology.